Place-names in the Soviet Arctic - Armstrong, Terence (Polar Record, 1950)
There are places in the Soviet Arctic which on English maps and in English literature are called by three or four quite different names. The confusion to which this state of affairs leads is obvious. Yet it is not too difficult to establish a set of principles which might be generally used as a guide in putting Russian Arctic place-names on English maps.